2007
DOI: 10.1038/ncb1616
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step pericellular proteolysis controls the transition from individual to collective cancer cell invasion

Abstract: Invasive cell migration through tissue barriers requires pericellular remodelling of extracellular matrix (ECM) executed by cell-surface proteases, particularly membrane-type-1 matrix metalloproteinase (MT1-MMP/MMP-14). Using time-resolved multimodal microscopy, we show how invasive HT-1080 fibrosarcoma and MDA-MB-231 breast cancer cells coordinate mechanotransduction and fibrillar collagen remodelling by segregating the anterior force-generating leading edge containing beta1 integrin, MT1-MMP and F-actin from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
912
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(958 citation statements)
references
References 44 publications
40
912
2
4
Order By: Relevance
“…It has previously been shown that the degradation of the ECM occurs at the tips of the pseudopodia, which directs the translocation of cells (Wolf et al, 2007). In WAVE2-and Arp3-depleted cells, thinner pseudopodia were formed, which did not allow cell locomotion (Figures 2d and 6e).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has previously been shown that the degradation of the ECM occurs at the tips of the pseudopodia, which directs the translocation of cells (Wolf et al, 2007). In WAVE2-and Arp3-depleted cells, thinner pseudopodia were formed, which did not allow cell locomotion (Figures 2d and 6e).…”
Section: Discussionmentioning
confidence: 88%
“…The latter phosphorylates the myosin-II light chain and consequently leads to actomyosin contractility, and this process that is independent of protease activity Sabeh et al, 2004;Wilkinson et al, 2005;Carragher et al, 2006;Paluch et al, 2006;Torka et al, 2006;Wyckoff et al, 2006;Sahai et al, 2007;Fackler and Grosse, 2008). Mesenchymal motility can also switch to amoeboid motility if pericellular proteolysis is blocked by treatment with protease inhibitors (Wolf et al, , 2007Carragher et al, 2006). With regard to morphological features, cells exhibiting mesenchymal motility develop elongated pseudopodia that extend into the ECM, whereas cells exhibiting amoeboid motility form bleb-like protrusions that extend into the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve extracellular matrix remodeling, mesenchymal cells, such as solid tumor cells and fibroblasts, have developed a strategy to pericellularly remodel and proteolytically degrade the extracellular matrix using matrix metalloproteinases (MMPs) [114]. Cancer cells were shown to coordinate mechanotransduction and extracellular matrix remodeling by segregating the anterior force-generating leading edge containing integrins, F-actin and the membrane type 1 (MT1)-MMP from the posterior proteolytic zone where extracellular matrix fibers are cleaved [116]. Of note, the delivery of MT1-MMP to the leading invasive pseudopods of a migrating cell is coordinated by the NPF Neural Wiskott Aldrich syndrome protein (N-WASP) [117].…”
Section: Trafficking Of Other Cell Surface Adhesions Proteinsmentioning
confidence: 99%
“…To date, most cell migration experiments in 3D with live cell imaging are performed in open multiwell systems, chamber slides (Zaman et al 2006), or custom-made sealed chambers Gunzer et al 1997;Wolf et al 2007) which do not readily permit the application of welldefined external chemical gradients. Modified Boyden chambers for 3D cell invasion (Semino et al 2006;Shields et al 2007) are not conducive to live cell imaging and therefore key parameters like migration speed, persistence ratio, and percentage of migratory cells remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%